Hubungan Antara Pemberian Asi Eksklusif Dan Pengetahuan Ibu Dengan Kejadian Campak Pada Balita Di Kabupaten Sukoharjo - Prabowati, Elly, Bejo Raharjo, SKM, M.Kes, Anisa Catur Wijayanti, SKM., M.Epid (2016)
Measles is contagious respiratory disease into the public health problem for infants and child. Measles virus transmitted through thw air when a patient coughs and sneezes. Confrim elasles is measles disease which eans diagnosis using serological test in laboratory. The research was purposed the exclusive breast-feeding and mother's knowledge toward the measles which is attacked infant in Sukoharjo District. The method used the obervasional with case control design. Responden group drawn from the case of infants that affected measles aged 6-59 month as much 55 infants. The result showed that the test analysis Chi square there was the relationship between exclusive breast-feeding (p=0,036; OR=2,435; 95% CI=1,130-5,245) and there was not relationship between the mother's knowledge (p=0,081) toward the infants measles